Silencing of activism in Australian law. (September 2017) - Heath, Mary; Burdon, Peter
Environmental destruction and climate change are driving new waves of environmental activism. In response, governments in several Australian states have enacted legislation designed to penalise and silence political protest. This article analyses Tasmania's anti-protest laws and considers how the United Nations and scholars have reacted to them. We argue that protest suppression laws such as these reflect a neoliberal rationality which conceptualises society in market terms. This mode of thinking perceives protest as market interference rather than civic participation. Accordingly, anti-protest laws seek to secure the rights and interests of corporations to unimpeded market access.